Optical and electrical transport properties of α-Ga2O3 thin films with electrical compensation of Sn impurities - Wentian Cao; Xiaoqi Qin; Shuyun Wang (AIP Advances)
Polycrystalline α-Ga2O3 thin films containing secondary phase SnO were grown on BaF2 substrates by magnetron sputtering. The impurity tin concentration, electron concentration, and room temperature mobility of the α-Ga2O3 films are 4.5 × 1020 cm−3, 1.5 × 1015 cm−3, and 26.9 cm2 V−1 s−1, respectively, determined by secondary ion mass spectrometry and Hall effect experiments. The mobility vs temperature dependence confirms that the electrons are mainly subject to polar optical phonon scattering and ionized impurity scattering in the temperature range of 160–400 K. Two ionization energies, 29 and 71 meV, were determined for different temperature ranges by logarithmic resistivity vs the reciprocal of temperature, where the former is the shallow donor SnGa formed by the incorporation of tin into gallium sites. The latter is the shallow acceptor VSn–H associated with secondary phase SnO, and it is the electrical compensation of this shallow acceptor that results in the very low carrier concentration of α-Ga2O3 films. The photoluminescence spectrum exhibits 280 and 320 nm UV radiation, where 280 nm is due to the radiation recombination of electrons trapped by the deep donor state (EC−1.1 eV) with holes trapped by the VSn–H complex. In addition, there are several narrow radiation peaks in the visible region, and the energy levels involved in the radiation transitions are determined one by one after excluding the effects of interference and diffraction.